Skin-friendly anti-static fiber fabric, preparation method thereof and application of skin-friendly anti-static fiber fabric in traceless underwear

By mixing modified polyacrylonitrile, norbornene and modified graphene oxide, spinning and twisting with cotton yarn core, and impregnating with hyaluronic acid, a skin-friendly and anti-static fiber fabric is produced, which solves the problem of hard and static feel of underwear after washing, and achieves good anti-static, skin-friendly and anti-bacterial effects.

CN119686113AInactive Publication Date: 2025-03-25GUANGDONG QICAIFEIXIA KNITTING IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510209126.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-25
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing underwear feels hard after washing, it feels uncomfortable when directly touching the skin, and is prone to static electricity, affecting human health.

Method used

Modified polyacrylonitrile, norbornene and modified graphene oxide were mixed and spinned and twisted with cotton yarn core, and impregnated with hyaluronic acid to make skin-friendly and anti-static fiber fabric.

Benefits of technology

It realizes excellent antistatic and skin-friendly properties of fiber fabrics, while improving the mechanical properties and antibacterial properties of the fabrics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
  • Figure SMS_6
    Figure SMS_6
Patent Text Reader

Abstract

The invention discloses a skin-friendly anti-static fiber fabric, a preparation method thereof and application of the skin-friendly anti-static fiber fabric in traceless underwear, and relates to the field of fabrics. When the skin-friendly anti-static fiber fabric is prepared, graphene oxide is subjected to carboxylation and then is grafted with 4-amino-1-allylpyrazole, and modified graphene oxide is prepared; the preparation method comprises the following steps: treating polyacrylonitrile with sodium hydroxide, and grafting (2-aminoethyl) trimethyl ammonium chloride hydrochloride and 5-norbornene-2-methylamine to prepare modified polyacrylonitrile; uniformly mixing modified polyacrylonitrile, norbornene and modified graphene oxide, spinning, and twisting with a cotton yarn core to obtain a covering yarn; treating the covering yarn with hyaluronic acid, and spinning to obtain the skin-friendly anti-static fiber fabric. The skin-friendly anti-static fiber fabric prepared by the invention has excellent skin-friendly property, antibacterial property, anti-static property, mechanical property and shape memory property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fabrics, in particular to a skin-friendly antistatic fiber fabric and a preparation method thereof and application in seamless underwear. Background Art

[0002] With the rapid development of economy and the improvement of people's living standards, the demand for underwear has developed from the initial basic physiological functions such as covering the body and keeping warm to the stage of pursuing more beautiful, quality, comfort, fashion and high-end, and seamless body shaping underwear has developed rapidly. As the name suggests, seamless underwear is traceless, and the traditional sewing process is often replaced by no seams or bonding with Bemis. The underwear is comfortable to wear, free to move, seamless and traceless, avoiding the underwear or body contour being exposed due to the discomfort of tightness when wearing traditional underwear, and the laminating process at the seam will not be constrained by the stitches like traditional sewing and stretching is not free. Most clothes feel hard after washing, especially underwear, which is very uncomfortable to directly contact the skin. Static electricity will also be generated during wearing, which is manifested as sparks, electric shock sensation, thin clothes in summer sticking to the body, etc., which affects human health. Therefore, the present invention prepares a skin-friendly fiber fabric with excellent antistatic properties. Summary of the invention

[0003] The purpose of the present invention is to provide a skin-friendly antistatic fiber fabric and a preparation method thereof and application in seamless underwear, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions: a skin-friendly antistatic fiber fabric, which is obtained by mixing modified polyacrylonitrile, norbornene, and modified graphene oxide, spinning them, twisting them with a cotton yarn core, and then impregnating them with hyaluronic acid.

[0005] As an optimization, the cotton yarn core model is 40 count and comes from Shandong Huamian Yarn Co., Ltd.

[0006] As an optimization, the modified polyacrylonitrile is prepared by treating polyacrylonitrile with sodium hydroxide and then grafting (2-aminoethyl)trimethylammonium chloride hydrochloride and 5-norbornene-2-methylamine.

[0007] As an optimization, the polyacrylonitrile model is an industrial-grade powder from Hubei Shineng Chemical Technology Co., Ltd.

[0008] As an optimization, the modified graphene oxide is prepared by carboxylating graphene oxide and then grafting 4-amino-1-allylpyrazole.

[0009] As an optimization, the graphene oxide model is nanoscale and comes from Lingshou County Jianshi Mineral Powder Factory.

[0010] A method for preparing a skin-friendly antistatic fiber fabric comprises the following preparation steps: (1) Graphene oxide and deionized water were mixed in a mass ratio of 1: (350-450), ultrasonically dispersed for 25-35 min, hydrobromic acid 45-55 times the mass of graphene oxide was added, stirred at 30-40 ° C and 300-500 rpm for 9-11 h, oxalic acid 10-20 times the mass of graphene oxide was added, the temperature was raised to 60-80 ° C and continued to stir for 4-6 h, naturally cooled to room temperature and filtered, washed with deionized water for 3-5 times, and dried at 50-60 ° C for 19-21 h to obtain carboxylated graphene oxide; (2) Carboxylated graphene oxide, 4-amino-1-allylpyrazole, N,N'-dicyclohexylcarbodiimide and N,N-dimethylformamide are mixed in a mass ratio of 1: (7-8): (14-15): (900-1100), ultrasonically dispersed at 20-30°C for 15-25 min, stirred at 55-65°C and 200-400 rpm for 23-25 ​​h, cooled naturally to room temperature and centrifuged, washed with N,N-dimethylformamide and deionized water for 3-5 times respectively, and freeze-dried to obtain modified graphene oxide; (3) Mix polyacrylonitrile, sodium hydroxide and deionized water in a mass ratio of 1: (9-11): (95-105), stir at 65-75°C and 100-300 rpm for 1-3 hours, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 3-5 times respectively, and dry at 55-65°C for 11-13 hours to obtain pre-modified polyacrylonitrile; mix pre-modified polyacrylonitrile, (2-aminoethyl) trimethylammonium chloride hydrochloride, 5-norbornene-2-methylamine and toluene in a mass ratio of 1: (5-7): (5-6): (90-110), reflux at 65-75°C for 11-13 hours, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 3-5 times respectively, and dry at 55-65°C for 11-13 hours to obtain modified polyacrylonitrile; (4) Modified polyacrylonitrile, norbornene, modified graphene oxide, diisopropylbenzene peroxide and N,N-dimethylformamide are mixed in a mass ratio of 1: (0.02-0.04): (0.03-0.05): (0.01-0.02): (8-9) to obtain a spinning solution; the spinning solution is subjected to electrostatic spinning, twisted with a cotton yarn core, allowed to stand at 50-60°C for 3-5 hours, washed with deionized water for 3-5 times, and dried at 55-65°C for 11-13 hours to obtain a core-spun yarn; (5) The core-spun yarn was immersed in the hyaluronic acid mixture for 10-20 min, then taken out and dried until no liquid drops fell within 5-15 s. The yarn was placed at 40-50 °C for 6-8 h, washed with deionized water for 3-5 times, and dried at 55-65 °C for 11-13 h to obtain a spun yarn. The spun yarn was woven with a Santoni seamless knitting underwear machine SM8-TOP2 into a warp density of 550-650 yarns / 10 cm, a weft density of 450-550 yarns / 10 cm, and a weight of 200-300 g / m 2 The single-layer plain weave fabric is used to obtain a skin-friendly and antistatic fiber fabric.

[0011] As an optimization, the reaction equation for carboxylating graphene oxide in step (1) is: .

[0012] As an optimization, the reaction equation for modifying graphene oxide in step (2) is: .

[0013] As an optimization, the reaction equation of the pre-modified polyacrylonitrile in step (3) is: .

[0014] As an optimization, the reaction equation for modifying polyacrylonitrile in step (3) is: .

[0015] As an optimization, the process parameters of the electrospinning in step (4) are: solution flow rate 1.1~1.3ml / h, spinning voltage 9.7~9.9kv, spinning distance 15~25cm, collecting distance 10~18cm, receiving ring speed 300~600r / min, winding speed 1~3m / min, temperature 21~25℃, and humidity 55~65%.

[0016] As an optimization, the hyaluronic acid mixed solution in step (5) is obtained by mixing hyaluronic acid, copper chloride and deionized water in a mass ratio of 1: (0.1-0.3): (8-10), and adding 4%-6% acetic acid solution to adjust the pH of the solution to 4-5.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: when preparing the skin-friendly antistatic fiber fabric, the present invention carboxylates graphene oxide and then grafts 4-amino-1-allylpyrazole to obtain modified graphene oxide; polyacrylonitrile is treated with sodium hydroxide and then grafted with (2-aminoethyl)trimethylammonium chloride hydrochloride and 5-norbornene-2-methylamine to obtain modified polyacrylonitrile; the modified polyacrylonitrile, norbornene and modified graphene oxide are mixed and then spun and twisted with a cotton yarn core to obtain a core-spun yarn; the core-spun yarn is treated with hyaluronic acid and then spun to obtain the skin-friendly antistatic fiber fabric.

[0018] Firstly, graphene oxide was carboxylated and then grafted with 4-amino-1-allylpyrazole to obtain modified graphene oxide; polyacrylonitrile was treated with sodium hydroxide and then grafted with (2-aminoethyl)trimethylammonium chloride hydrochloride and 5-norbornene-2-methylamine to obtain modified polyacrylonitrile; graphene oxide was used as a reinforcing phase to enrich the conductive channels and improve the antistatic properties of the skin-friendly antistatic fiber fabric; the epoxy groups were ring-opened with hydrobromic acid to be converted into hydroxyl groups, and then esterified with oxalic acid to convert the oxygen-containing groups on the surface of graphene oxide into carboxyl groups, and 4-amino- 1-allylpyrazole, the amide bond can form hydrogen bond cross-links with hydroxyl and carboxyl groups, and can also complex metal ions to improve the mechanical properties of skin-friendly antistatic fiber fabrics; at the same time, the introduction of carbon-carbon double bonds can be polymerized and grafted with norbornene to form cross-links, thereby improving the mechanical properties of skin-friendly antistatic fiber fabrics; conjugated pyrazole rings can destroy cell membrane functions and improve the antibacterial properties of skin-friendly antistatic fiber fabrics; (2-aminoethyl)trimethylammonium chloride is grafted on the surface of polyacrylonitrile, and quaternary ammonium cations are used to eliminate or reduce electrostatic charges, thereby improving the antistatic properties of skin-friendly antistatic fiber fabrics.

[0019] Secondly, modified polyacrylonitrile, norbornene and modified graphene oxide are mixed and spun and twisted with cotton yarn core to obtain core-spun yarn; the core-spun yarn is treated with hyaluronic acid and then spun to obtain skin-friendly antistatic fiber fabric; diisopropylbenzene peroxide is used to induce unsaturated double bond crosslinking to form a covalent crosslinking network of norbornene, which weakens the internal stress and rearranges the molecular chain when the temperature rises, thereby improving the shape memory of the skin-friendly antistatic fiber fabric; the core-spun yarn is obtained by using pure cotton as the yarn core to enhance the water absorption of the yarn and improve the antistatic property of the skin-friendly antistatic fiber fabric; the spun yarn is finished with hyaluronic acid and copper ions, which are natural substances with good biocompatibility, and the copper ions are complexed by hydroxyl, carboxyl and amide to form a crosslinking network between the cotton fiber, the polyacrylonitrile main chain and the hyaluronic acid, thereby enhancing the binding force between the yarn core and the shell layer, and improving the skin-friendly and mechanical properties of the skin-friendly antistatic fiber fabric; at the same time, copper ions can interfere with protein function, destroy DNA in cells, and improve the antibacterial property of the skin-friendly antistatic fiber fabric. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] The raw materials used in the following examples and comparative examples are all commercially available: the graphene oxide model is nano-grade and comes from Lingshou County Jianshi Mineral Powder Factory; the polyacrylonitrile model is industrial-grade powder and comes from Hubei Shineng Chemical Technology Co., Ltd.; the cotton yarn core model is 40s and comes from Shandong Huamian Yarn Co., Ltd.

[0022] Example 1 A method for preparing a skin-friendly antistatic fiber fabric, the method comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:350, ultrasonically dispersed for 25 min, hydrobromic acid 45 times the mass of graphene oxide was added, stirred at 30 ° C and 300 rpm for 11 h, oxalic acid 10 times the mass of graphene oxide was added, the temperature was raised to 60 ° C and continued to stir for 6 h, naturally cooled to room temperature and filtered, washed with deionized water 3 times, and dried at 50 ° C for 21 h to obtain carboxylated graphene oxide; (2) Carboxylated graphene oxide, 4-amino-1-allylpyrazole, N,N'-dicyclohexylcarbodiimide and N,N-dimethylformamide were mixed in a mass ratio of 1:7:14:900, ultrasonically dispersed at 20°C for 25 min, stirred at 55°C and 200 rpm for 25 h, cooled naturally to room temperature and centrifuged, washed with N,N-dimethylformamide and deionized water for three times respectively, and freeze-dried to obtain modified graphene oxide; (3) Polyacrylonitrile, sodium hydroxide and deionized water were mixed in a mass ratio of 1:9:95, stirred at 65°C and 100 rpm for 3 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 3 times respectively, and dried at 55°C for 13 h to obtain pre-modified polyacrylonitrile; pre-modified polyacrylonitrile, (2-aminoethyl)trimethylammonium chloride hydrochloride, 5-norbornene-2-methylamine and toluene were mixed in a mass ratio of 1:5:5:90, refluxed at 65°C for 13 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 3 times respectively, and dried at 55°C for 13 h to obtain modified polyacrylonitrile; (4) Modified polyacrylonitrile, norbornene, modified graphene oxide, diisopropylbenzene peroxide and N,N-dimethylformamide were mixed in a mass ratio of 1:0.02:0.03:0.01:8 to obtain a spinning solution; the spinning solution was electrospun under the conditions of solution flow rate 1.1 ml / h, spinning voltage 9.7 kv, spinning distance 15 cm, collecting distance 10 cm, receiving ring speed 300 r / min, winding speed 1 m / min, temperature 21 °C, and humidity 55%, and twisted with a cotton yarn core, allowed to stand at 50 °C for 5 h, washed with deionized water 3 times, and dried at 55 °C for 13 h to obtain a core-spun yarn; (5) Hyaluronic acid, copper chloride and deionized water were mixed in a mass ratio of 1:0.1:8, and a 4% by mass acetic acid solution was added to adjust the pH of the solution to 4 to obtain a hyaluronic acid mixed solution; the core-spun yarn was immersed in the hyaluronic acid mixed solution for 10 minutes, then taken out, and aired until no droplets fell within 5 seconds, and then allowed to stand at 40°C for 8 hours, washed with deionized water for 3 times, and dried at 55°C for 13 hours to obtain a spun yarn; the spun yarn was woven with a Santoni seamless knitting underwear machine SM8-TOP2 into a warp density of 550 yarns / 10cm, a weft density of 450 yarns / 10cm, and a thickness of 200g / m 2 The single-layer plain weave fabric is used to obtain a skin-friendly and antistatic fiber fabric.

[0023] Example 2 A method for preparing a skin-friendly antistatic fiber fabric, the method comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:400, ultrasonically dispersed for 30 min, hydrobromic acid 50 times the mass of graphene oxide was added, stirred at 35 ° C and 400 rpm for 10 h, oxalic acid 15 times the mass of graphene oxide was added, the temperature was raised to 70 ° C and continued to stir for 5 h, naturally cooled to room temperature and filtered, washed with deionized water 4 times, and dried at 55 ° C for 20 h to obtain carboxylated graphene oxide; (2) Carboxylated graphene oxide, 4-amino-1-allylpyrazole, N,N'-dicyclohexylcarbodiimide and N,N-dimethylformamide were mixed in a mass ratio of 1:7.5:14.5:1000, ultrasonically dispersed at 25°C for 20 min, stirred at 60°C and 300 rpm for 24 h, cooled naturally to room temperature and centrifuged, washed with N,N-dimethylformamide and deionized water for 4 times respectively, and freeze-dried to obtain modified graphene oxide; (3) Polyacrylonitrile, sodium hydroxide and deionized water were mixed in a mass ratio of 1:10:100, stirred at 70°C and 200 rpm for 2 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 60°C for 12 h to obtain pre-modified polyacrylonitrile; pre-modified polyacrylonitrile, (2-aminoethyl)trimethylammonium chloride hydrochloride, 5-norbornene-2-methylamine and toluene were mixed in a mass ratio of 1:6:5.5:100, refluxed at 70°C for 12 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 60°C for 12 h to obtain modified polyacrylonitrile; (4) Modified polyacrylonitrile, norbornene, modified graphene oxide, diisopropylbenzene peroxide and N,N-dimethylformamide were mixed in a mass ratio of 1:0.03:0.04:0.015:8.5 to obtain a spinning solution; the spinning solution was electrospun under the conditions of solution flow rate 1.2 ml / h, spinning voltage 9.8 kv, spinning distance 20 cm, collecting distance 14 cm, receiving ring speed 450 r / min, winding speed 2 m / min, temperature 23 ° C, and humidity 60%, and twisted with a cotton yarn core, allowed to stand at 55 ° C for 4 h, washed with deionized water 4 times, and dried at 60 ° C for 12 h to obtain a core-spun yarn; (5) Hyaluronic acid, copper chloride and deionized water were mixed in a mass ratio of 1:0.2:9, and a 5% by mass acetic acid solution was added to adjust the pH of the solution to 4.5 to obtain a hyaluronic acid mixed solution; the core-spun yarn was immersed in the hyaluronic acid mixed solution for 15 minutes, then taken out, and aired until no droplets fell within 10 seconds, and then allowed to stand at 45°C for 7 hours, washed with deionized water for 4 times, and dried at 60°C for 12 hours to obtain a spun yarn; the spun yarn was woven with a Santoni seamless knitting underwear machine SM8-TOP2 into a warp density of 600 yarns / 10cm, a weft density of 500 yarns / 10cm, and a weight of 250g / m 2 The single-layer plain weave fabric is used to obtain a skin-friendly and antistatic fiber fabric.

[0024] Example 3 A method for preparing a skin-friendly antistatic fiber fabric, the method comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:450, ultrasonically dispersed for 35 min, hydrobromic acid 55 times the mass of graphene oxide was added, stirred at 40 ° C and 500 rpm for 9 h, oxalic acid 20 times the mass of graphene oxide was added, the temperature was raised to 80 ° C and stirred for 4 h, naturally cooled to room temperature and filtered, washed with deionized water 5 times, and dried at 60 ° C for 19 h to obtain carboxylated graphene oxide; (2) Carboxylated graphene oxide, 4-amino-1-allylpyrazole, N,N'-dicyclohexylcarbodiimide and N,N-dimethylformamide were mixed in a mass ratio of 1:8:15:1100, ultrasonically dispersed at 30°C for 15 min, stirred at 65°C and 400 rpm for 23 h, cooled naturally to room temperature and centrifuged, washed with N,N-dimethylformamide and deionized water for 5 times respectively, and freeze-dried to obtain modified graphene oxide; (3) Polyacrylonitrile, sodium hydroxide and deionized water were mixed in a mass ratio of 1:11:105, stirred at 75°C and 300 rpm for 1 hour, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 5 times respectively, and dried at 65°C for 11 hours to obtain pre-modified polyacrylonitrile; pre-modified polyacrylonitrile, (2-aminoethyl)trimethylammonium chloride hydrochloride, 5-norbornene-2-methylamine and toluene were mixed in a mass ratio of 1:7:6:110, refluxed at 75°C for 11 hours, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 5 times respectively, and dried at 65°C for 11 hours to obtain modified polyacrylonitrile; (4) Modified polyacrylonitrile, norbornene, modified graphene oxide, diisopropylbenzene peroxide and N,N-dimethylformamide were mixed in a mass ratio of 1:0.04:0.05:0.02:9 to obtain a spinning solution; the spinning solution was electrospun under the conditions of solution flow rate 1.3 ml / h, spinning voltage 9.9 kv, spinning distance 25 cm, collecting distance 18 cm, receiving ring speed 600 r / min, winding speed 3 m / min, temperature 25 ° C, and humidity 65%, and twisted with a cotton yarn core, allowed to stand at 60 ° C for 3 h, washed with deionized water 5 times, and dried at 65 ° C for 11 h to obtain a core-spun yarn; (5) Hyaluronic acid, copper chloride and deionized water were mixed in a mass ratio of 1:0.3:10, and a 6% by mass acetic acid solution was added to adjust the pH of the solution to 5 to obtain a hyaluronic acid mixed solution; the core-spun yarn was immersed in the hyaluronic acid mixed solution for 20 minutes, then taken out, and aired until no droplets fell within 15 seconds, and then allowed to stand at 50°C for 6 hours, washed with deionized water for 5 times, and dried at 65°C for 11 hours to obtain a spun yarn; the spun yarn was woven with a Santoni seamless knitting underwear machine SM8-TOP2 into a warp density of 650 yarns / 10cm, a weft density of 550 yarns / 10cm, and a thickness of 300g / m 2 The single-layer plain weave fabric is used to obtain a skin-friendly and antistatic fiber fabric.

[0025] Comparative Example 1: A method for preparing a skin-friendly antistatic fiber fabric, the method comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:400, ultrasonically dispersed for 30 min, hydrobromic acid 50 times the mass of graphene oxide was added, stirred at 35 ° C and 400 rpm for 10 h, oxalic acid 15 times the mass of graphene oxide was added, the temperature was raised to 70 ° C and continued to stir for 5 h, naturally cooled to room temperature and filtered, washed with deionized water 4 times, and dried at 55 ° C for 20 h to obtain carboxylated graphene oxide; (2) Polyacrylonitrile, sodium hydroxide and deionized water were mixed in a mass ratio of 1:10:100, stirred at 70°C and 200 rpm for 2 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 60°C for 12 h to obtain pre-modified polyacrylonitrile; pre-modified polyacrylonitrile, (2-aminoethyl)trimethylammonium chloride hydrochloride, 5-norbornene-2-methylamine and toluene were mixed in a mass ratio of 1:6:5.5:100, refluxed at 70°C for 12 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 60°C for 12 h to obtain modified polyacrylonitrile; (3) Modified polyacrylonitrile, norbornene, carboxylated graphene oxide, diisopropylbenzene peroxide and N,N-dimethylformamide were mixed in a mass ratio of 1:0.03:0.04:0.015:8.5 to obtain a spinning solution; the spinning solution was electrospun under the conditions of solution flow rate 1.2 ml / h, spinning voltage 9.8 kv, spinning distance 20 cm, collecting distance 14 cm, receiving ring speed 450 r / min, winding speed 2 m / min, temperature 23 °C, and humidity 60%, and twisted with a cotton yarn core, allowed to stand at 55 °C for 4 h, washed with deionized water 4 times, and dried at 60 °C for 12 h to obtain a core-spun yarn; (4) Hyaluronic acid, copper chloride and deionized water were mixed in a mass ratio of 1:0.2:9, and a 5% by mass acetic acid solution was added to adjust the pH of the solution to 4.5 to obtain a hyaluronic acid mixed solution; the core-spun yarn was immersed in the hyaluronic acid mixed solution for 15 minutes, then taken out, and aired until no droplets fell within 10 seconds, and then allowed to stand at 45°C for 7 hours, washed with deionized water for 4 times, and dried at 60°C for 12 hours to obtain a spun yarn; the spun yarn was woven with a Santoni seamless knitting underwear machine SM8-TOP2 into a warp density of 600 yarns / 10cm, a weft density of 500 yarns / 10cm, and a weight of 250g / m 2 The single-layer plain weave fabric is used to obtain a skin-friendly and antistatic fiber fabric.

[0026] Comparative Example 2: A method for preparing a skin-friendly antistatic fiber fabric, the method comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:400, ultrasonically dispersed for 30 min, hydrobromic acid 50 times the mass of graphene oxide was added, stirred at 35 ° C and 400 rpm for 10 h, oxalic acid 15 times the mass of graphene oxide was added, the temperature was raised to 70 ° C and continued to stir for 5 h, naturally cooled to room temperature and filtered, washed with deionized water 4 times, and dried at 55 ° C for 20 h to obtain carboxylated graphene oxide; (2) Carboxylated graphene oxide, 4-amino-1-allylpyrazole, N,N'-dicyclohexylcarbodiimide and N,N-dimethylformamide were mixed in a mass ratio of 1:7.5:14.5:1000, ultrasonically dispersed at 25°C for 20 min, stirred at 60°C and 300 rpm for 24 h, cooled naturally to room temperature and centrifuged, washed with N,N-dimethylformamide and deionized water for 4 times respectively, and freeze-dried to obtain modified graphene oxide; (3) Mix polyacrylonitrile, sodium hydroxide and deionized water in a mass ratio of 1:10:100, stir at 70°C and 200 rpm for 2 h, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 4 times respectively, and dry at 60°C for 12 h to obtain pre-modified polyacrylonitrile; mix pre-modified polyacrylonitrile, (2-aminoethyl)trimethylammonium chloride hydrochloride and toluene in a mass ratio of 1:6:100, reflux at 70°C for 12 h, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 4 times respectively, and dry at 60°C for 12 h to obtain modified polyacrylonitrile; (4) Modified polyacrylonitrile, modified graphene oxide and N,N-dimethylformamide were mixed in a mass ratio of 1:0.04:8.5 to obtain a spinning solution; the spinning solution was electrospun under the conditions of solution flow rate 1.2 ml / h, spinning voltage 9.8 kv, spinning distance 20 cm, collecting distance 14 cm, receiving ring speed 450 r / min, winding speed 2 m / min, temperature 23 ° C, and humidity 60%, twisted with a cotton yarn core, allowed to stand at 55 ° C for 4 h, washed with deionized water 4 times, and dried at 60 ° C for 12 h to obtain a core-spun yarn; (5) Hyaluronic acid, copper chloride and deionized water were mixed in a mass ratio of 1:0.2:9, and a 5% by mass acetic acid solution was added to adjust the pH of the solution to 4.5 to obtain a hyaluronic acid mixed solution; the core-spun yarn was immersed in the hyaluronic acid mixed solution for 15 minutes, then taken out, and aired until no droplets fell within 10 seconds, and then allowed to stand at 45°C for 7 hours, washed with deionized water for 4 times, and dried at 60°C for 12 hours to obtain a spun yarn; the spun yarn was woven with a Santoni seamless knitting underwear machine SM8-TOP2 into a warp density of 600 yarns / 10cm, a weft density of 500 yarns / 10cm, and a weight of 250g / m 2 The single-layer plain weave fabric is used to obtain a skin-friendly and antistatic fiber fabric.

[0027] Comparative Example 3: A method for preparing a skin-friendly antistatic fiber fabric, the method comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:400, ultrasonically dispersed for 30 min, hydrobromic acid 50 times the mass of graphene oxide was added, stirred at 35 ° C and 400 rpm for 10 h, oxalic acid 15 times the mass of graphene oxide was added, the temperature was raised to 70 ° C and continued to stir for 5 h, naturally cooled to room temperature and filtered, washed with deionized water 4 times, and dried at 55 ° C for 20 h to obtain carboxylated graphene oxide; (2) Carboxylated graphene oxide, 4-amino-1-allylpyrazole, N,N'-dicyclohexylcarbodiimide and N,N-dimethylformamide were mixed in a mass ratio of 1:7.5:14.5:1000, ultrasonically dispersed at 25°C for 20 min, stirred at 60°C and 300 rpm for 24 h, cooled naturally to room temperature and centrifuged, washed with N,N-dimethylformamide and deionized water for 4 times respectively, and freeze-dried to obtain modified graphene oxide; (3) Mix polyacrylonitrile, sodium hydroxide and deionized water in a mass ratio of 1:10:100, stir at 70°C and 200 rpm for 2 hours, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 4 times, and dry at 60°C for 12 hours to obtain pre-modified polyacrylonitrile; mix pre-modified polyacrylonitrile, 5-norbornene-2-methylamine and toluene in a mass ratio of 1:5.5:100, reflux at 70°C for 12 hours, cool naturally to room temperature and filter, wash with anhydrous ethanol and deionized water for 4 times, and dry at 60°C for 12 hours to obtain modified polyacrylonitrile; (4) Modified polyacrylonitrile, norbornene, modified graphene oxide, diisopropylbenzene peroxide and N,N-dimethylformamide were mixed in a mass ratio of 1:0.03:0.04:0.015:8.5 to obtain a spinning solution; the spinning solution was electrospun under the conditions of solution flow rate 1.2 ml / h, spinning voltage 9.8 kv, spinning distance 20 cm, collecting distance 14 cm, receiving ring speed 450 r / min, winding speed 2 m / min, temperature 23 ° C, and humidity 60%, and twisted with a cotton yarn core, allowed to stand at 55 ° C for 4 h, washed with deionized water 4 times, and dried at 60 ° C for 12 h to obtain a core-spun yarn; (5) Hyaluronic acid, copper chloride and deionized water were mixed in a mass ratio of 1:0.2:9, and a 5% by mass acetic acid solution was added to adjust the pH of the solution to 4.5 to obtain a hyaluronic acid mixed solution; the core-spun yarn was immersed in the hyaluronic acid mixed solution for 15 minutes, then taken out, and aired until no droplets fell within 10 seconds, and then allowed to stand at 45°C for 7 hours, washed with deionized water for 4 times, and dried at 60°C for 12 hours to obtain a spun yarn; the spun yarn was woven with a Santoni seamless knitting underwear machine SM8-TOP2 into a warp density of 600 yarns / 10cm, a weft density of 500 yarns / 10cm, and a weight of 250g / m 2 The single-layer plain weave fabric is used to obtain a skin-friendly and antistatic fiber fabric.

[0028] Comparative Example 4: A method for preparing a skin-friendly antistatic fiber fabric, the method comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:400, ultrasonically dispersed for 30 min, hydrobromic acid 50 times the mass of graphene oxide was added, stirred at 35 ° C and 400 rpm for 10 h, oxalic acid 15 times the mass of graphene oxide was added, the temperature was raised to 70 ° C and continued to stir for 5 h, naturally cooled to room temperature and filtered, washed with deionized water 4 times, and dried at 55 ° C for 20 h to obtain carboxylated graphene oxide; (2) Carboxylated graphene oxide, 4-amino-1-allylpyrazole, N,N'-dicyclohexylcarbodiimide and N,N-dimethylformamide were mixed in a mass ratio of 1:7.5:14.5:1000, ultrasonically dispersed at 25°C for 20 min, stirred at 60°C and 300 rpm for 24 h, cooled naturally to room temperature and centrifuged, washed with N,N-dimethylformamide and deionized water for 4 times respectively, and freeze-dried to obtain modified graphene oxide; (3) Polyacrylonitrile, sodium hydroxide and deionized water were mixed in a mass ratio of 1:10:100, stirred at 70°C and 200 rpm for 2 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 60°C for 12 h to obtain pre-modified polyacrylonitrile; pre-modified polyacrylonitrile, (2-aminoethyl)trimethylammonium chloride hydrochloride, 5-norbornene-2-methylamine and toluene were mixed in a mass ratio of 1:6:5.5:100, refluxed at 70°C for 12 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 60°C for 12 h to obtain modified polyacrylonitrile; (4) Modified polyacrylonitrile, norbornene, modified graphene oxide, diisopropylbenzene peroxide and N,N-dimethylformamide were mixed in a mass ratio of 1:0.03:0.04:0.015:8.5 to obtain a spinning solution; the spinning solution was electrospun under the conditions of solution flow rate 1.2 ml / h, spinning voltage 9.8 kv, spinning distance 20 cm, collecting distance 14 cm, receiving ring speed 450 r / min, winding speed 2 m / min, temperature 23 ° C, and humidity 60%, and twisted with a cotton yarn core, allowed to stand at 55 ° C for 4 h, washed with deionized water 4 times, and dried at 60 ° C for 12 h to obtain a core-spun yarn; (5) Copper chloride and deionized water were mixed in a mass ratio of 0.2:9, and a 5% by mass acetic acid solution was added to adjust the pH value of the solution to 4.5 to obtain a mixed solution; the core-spun yarn was immersed in the mixed solution for 15 minutes, then taken out, and aired until no droplets fell within 10 seconds, and then allowed to stand at 45°C for 7 hours, washed with deionized water for 4 times, and dried at 60°C for 12 hours to obtain a spun yarn; the spun yarn was woven with a Santoni seamless knitting underwear machine SM8-TOP2 into a warp density of 600 yarns / 10cm, a weft density of 500 yarns / 10cm, and a weight of 250g / m 2 The single-layer plain weave fabric is used to obtain a skin-friendly and antistatic fiber fabric.

[0029] Comparative Example 5: A method for preparing a skin-friendly antistatic fiber fabric, the method comprising the following preparation steps: (1) Graphene oxide and deionized water were mixed at a mass ratio of 1:400, ultrasonically dispersed for 30 min, hydrobromic acid 50 times the mass of graphene oxide was added, stirred at 35 ° C and 400 rpm for 10 h, oxalic acid 15 times the mass of graphene oxide was added, the temperature was raised to 70 ° C and continued to stir for 5 h, naturally cooled to room temperature and filtered, washed with deionized water 4 times, and dried at 55 ° C for 20 h to obtain carboxylated graphene oxide; (2) Carboxylated graphene oxide, 4-amino-1-allylpyrazole, N,N'-dicyclohexylcarbodiimide and N,N-dimethylformamide were mixed in a mass ratio of 1:7.5:14.5:1000, ultrasonically dispersed at 25°C for 20 min, stirred at 60°C and 300 rpm for 24 h, cooled naturally to room temperature and centrifuged, washed with N,N-dimethylformamide and deionized water for 4 times respectively, and freeze-dried to obtain modified graphene oxide; (3) Polyacrylonitrile, sodium hydroxide and deionized water were mixed in a mass ratio of 1:10:100, stirred at 70°C and 200 rpm for 2 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 60°C for 12 h to obtain pre-modified polyacrylonitrile; pre-modified polyacrylonitrile, (2-aminoethyl)trimethylammonium chloride hydrochloride, 5-norbornene-2-methylamine and toluene were mixed in a mass ratio of 1:6:5.5:100, refluxed at 70°C for 12 h, naturally cooled to room temperature and filtered, washed with anhydrous ethanol and deionized water for 4 times respectively, and dried at 60°C for 12 h to obtain modified polyacrylonitrile; (4) Modified polyacrylonitrile, norbornene, modified graphene oxide, diisopropylbenzene peroxide and N,N-dimethylformamide were mixed in a mass ratio of 1:0.03:0.04:0.015:8.5 to obtain a spinning solution; the spinning solution was electrospun under the conditions of solution flow rate 1.2 ml / h, spinning voltage 9.8 kv, spinning distance 20 cm, collecting distance 14 cm, receiving ring speed 450 r / min, winding speed 2 m / min, temperature 23 ° C, and humidity 60%, and twisted with a cotton yarn core, allowed to stand at 55 ° C for 4 h, washed with deionized water 4 times, and dried at 60 ° C for 12 h to obtain a core-spun yarn; (5) Hyaluronic acid and deionized water were mixed in a mass ratio of 1:9, and a 5% by mass acetic acid solution was added to adjust the pH value of the solution to 4.5 to obtain a hyaluronic acid mixed solution; the core-spun yarn was immersed in the hyaluronic acid mixed solution for 15 minutes, then taken out, and aired until no droplets fell within 10 seconds, and then allowed to stand at 45°C for 7 hours, washed with deionized water for 4 times, and dried at 60°C for 12 hours to obtain a spun yarn; the spun yarn was woven with a Santoni seamless knitting underwear machine SM8-TOP2 into a warp density of 600 yarns / 10cm, a weft density of 500 yarns / 10cm, and a weight of 250g / m 2 The single-layer plain weave fabric is used to obtain a skin-friendly and antistatic fiber fabric.

[0030] Test Example 1: 1. Skin-friendly Test method: The skin-friendly antistatic fiber fabrics obtained in each embodiment and the control example are of the same size, ironed in a constant temperature and humidity laboratory at a temperature of 23°C and a humidity of 60%, and then balanced for 24 hours. The subjects adapt to the surrounding environment for 20 minutes to keep calm, touch the samples in sequence, and evaluate the touch of the fabric (not itchy, generally itchy, slightly itchy, very itchy, extremely itchy).

[0031] 2. Antistatic properties Test method: The skin-friendly antistatic fiber fabrics obtained in each embodiment and the comparative example were tested for volume resistivity using a YG321-1 fiber resistivity meter according to GB / T14342.

[0032] 3. Antibacterial Test method: Take 0.75g of the skin-friendly antistatic fiber fabric obtained in each embodiment and the comparative example of the same size and cut them into pieces as the sample to be tested. According to the GB / T20944 oscillation method, select Gram-negative Escherichia coli and culture them at 37°C for 18 hours to obtain a single isolated colony. On the solid culture medium, select a typical colony and transfer it to 20mL of liquid culture medium using an inoculation loop, and culture it at 37°C and an oscillation speed of 120r / min for 20 hours to obtain a bacterial solution with a specific number of viable bacteria. The sample was placed in a flask (no sample was added as the control group), 70 mL of PBS buffer and 5 mL of diluted bacterial solution with a specific number of viable bacteria were added, and then shaken on a shaker at 37°C and 120 rpm for 18 hours. Then, 100 μL of the bacterial suspension diluted to an appropriate multiple was taken and evenly coated on the surface of the solid culture medium. The suspension was cultured in a sterile environment at a constant temperature of 37°C for 24 hours. The single colonies on the solid culture medium were counted W1 (the viable bacteria concentration of the control group W0), and the inhibition rate Q0 = (W0-W1) / W0*100% was calculated.

[0033] Table 1 below shows the analysis results of the skin-friendly, antibacterial and antistatic properties of the skin-friendly antistatic fiber fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0034]

[0035] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 1, it can be found that the skin-friendly antistatic fiber fabric prepared by the present invention has good skin-friendly, antibacterial and antistatic properties.

[0036] By comparison, the antibacterial rates of Examples 1, 2, and 3 are higher than those of Comparative Example 1, indicating that the epoxy groups are opened with hydrobromic acid to be converted into hydroxyl groups, which are then esterified with oxalic acid to convert the oxygen-containing groups on the surface of graphene oxide into carboxyl groups, and 4-amino-1-allylpyrazole is grafted by amide reaction. The conjugated pyrazole ring can destroy the cell membrane function and improve the antibacterial property of the skin-friendly antistatic fiber fabric.

[0037] By comparison, the volume specific resistivity of Examples 1, 2, and 3 is lower than that of Comparative Example 3, indicating that (2-aminoethyl)trimethylammonium chloride is grafted on the surface of polyacrylonitrile, and the electrostatic charge is eliminated or reduced by quaternary ammonium cations, thereby improving the antistatic property of the skin-friendly antistatic fiber fabric.

[0038] By comparison, Examples 1, 2, and 3 have better touch and lower volume resistivity than Comparative Example 4, which indicates that the spun yarn is finished with hyaluronic acid, a natural substance with good biocompatibility, to enhance water absorption and improve the skin-friendly and antistatic properties of the skin-friendly antistatic fiber fabric.

[0039] By comparison, the antibacterial rates of Examples 1, 2, and 3 are higher than those of Comparative Example 5, indicating that copper ions can interfere with protein function, destroy intracellular DNA, and improve the antibacterial properties of the skin-friendly antistatic fiber fabric.

[0040] Test Example 2: 1. Mechanical properties Test method: The spun yarns obtained in each embodiment and the comparative example were tested for breaking strength using a YG005E electronic single fiber strength tester according to GB / T14337 at a clamping distance of 100 mm and a tensile speed of 100 mm / min.

[0041] 2. Shape memory Test method: The skin-friendly antistatic fiber fabrics obtained in each embodiment and the comparative example are of the same size, balanced at 35°C for 10 minutes, two points are marked in the middle, and the length L0 is measured; then stretched by 100%, the two ends are fixed, balanced at 5°C for 10 minutes, the two ends are loosened, and the fabrics are allowed to stand at 35°C for 10 minutes, and the distance L1 between the two marked points is measured; the shape recovery rate R=1-(L1-L0) / L0*100% is calculated.

[0042] Table 2 below shows the analysis results of the mechanical properties and shape memory of the skin-friendly antistatic fiber fabrics of Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0043]

[0044] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 5 in Table 2, it can be found that the skin-friendly antistatic fiber fabric prepared by the present invention has good mechanical properties and shape memory.

[0045] By comparison, Examples 1, 2, and 3 have higher breaking strength than Comparative Example 1, which indicates that the epoxy groups are ring-opened with hydrobromic acid to be converted into hydroxyl groups, which are then esterified with oxalic acid to convert the oxygen-containing groups on the surface of graphene oxide into carboxyl groups, and 4-amino-1-allylpyrazole is grafted using an amide reaction. The amide bond can form hydrogen bonds with hydroxyl and carboxyl groups, and can also complex metal ions to improve the mechanical properties of the skin-friendly antistatic fiber fabric. At the same time, the introduction of carbon-carbon double bonds can be polymerized and grafted with norbornene to form crosslinks, further improving the mechanical properties of the skin-friendly antistatic fiber fabric.

[0046] By comparison, the shape recovery rates of Examples 1, 2, and 3 are higher than those of Comparative Example 2, indicating that diisopropylbenzene peroxide is used to initiate unsaturated double bond crosslinking to form a covalent crosslinked network of norbornene. When the temperature rises, the internal stress is weakened and the molecular chains are rearranged, thereby improving the shape memory of the skin-friendly antistatic fiber fabric.

[0047] By comparison, the breaking strength of Examples 1, 2, and 3 is higher than that of Comparative Example 4, which illustrates that the spun yarn is finished with hyaluronic acid, a natural substance with good biocompatibility, and a cross-linked network is formed between the cotton fiber, the polyacrylonitrile main chain and the hyaluronic acid through the complexation of copper ions by hydroxyl, carboxyl and amide, thereby enhancing the bonding force between the yarn core and the shell layer and improving the mechanical properties of the skin-friendly antistatic fiber fabric.

[0048] By comparison, the breaking strength of Examples 1, 2, and 3 is higher than that of Comparative Example 5, which illustrates that the spun yarn is finished with copper ions to form a metal complex between hydroxyl groups, carboxyl groups, and amides, enrich the cross-linked network between cotton fibers, polyacrylonitrile main chains, and hyaluronic acid, enhance the bonding force between the yarn core and the shell layer, and improve the mechanical properties of the skin-friendly and antistatic fiber fabric.

[0049] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A skin-friendly antistatic fiber fabric, characterized in that: The skin-friendly antistatic fiber fabric is prepared by mixing modified polyacrylonitrile, norbornene and modified graphene oxide, spinning and twisting with a cotton yarn core, and then impregnating with hyaluronic acid; the modified polyacrylonitrile is prepared by treating polyacrylonitrile with sodium hydroxide and then grafting (2-aminoethyl)trimethylammonium chloride hydrochloride and 5-norbornene-2-methylamine; the modified graphene oxide is prepared by carboxylating graphene oxide and then grafting 4-amino-1-allylpyrazole.

2. A method for preparing a skin-friendly antistatic fiber fabric, characterized in that: The method comprises the following preparation steps: (1) Mix graphene oxide and deionized water, disperse by ultrasonication, add hydrobromic acid, stir at 30-40°C for 9-11 hours, add oxalic acid, heat to 60-80°C and continue stirring for 4-6 hours, cool to room temperature, filter, wash and dry to obtain carboxylated graphene oxide; (2) Mix carboxylated graphene oxide, 4-amino-1-allylpyrazole, N,N'-dicyclohexylcarbodiimide and N,N-dimethylformamide, disperse them by ultrasonication at 20-30°C, heat them to 55-65°C, stir them for 23-25h, cool them to room temperature, centrifuge them, wash and freeze-dry them to obtain modified graphene oxide; (3) Mix polyacrylonitrile, sodium hydroxide and deionized water, stir at 65-75°C for 1-3 hours, cool to room temperature, filter, wash and dry to obtain pre-modified polyacrylonitrile; Pre-modified polyacrylonitrile, (2-aminoethyl)trimethylammonium chloride hydrochloride, 5-norbornene-2-methylamine and toluene are mixed, refluxed at 65-75° C. for 11-13 hours, cooled to room temperature, filtered, washed and dried to obtain modified polyacrylonitrile; (4) mixing modified polyacrylonitrile, norbornene, modified graphene oxide, dicumyl peroxide and N,N-dimethylformamide to obtain a spinning solution; electrospinning the spinning solution, twisting it with a cotton yarn core, washing and drying it to obtain a core-spun yarn; (5) The core-spun yarn is immersed in a hyaluronic acid mixture, taken out, washed, and dried to obtain a spun yarn; and the spun yarn is woven into a skin-friendly antistatic fiber fabric using a Santoni seamless knitting underwear machine SM8-TOP2.

3. The method for preparing a skin-friendly antistatic fiber fabric according to claim 2, characterized in that: The carboxylated graphene oxide in step (1) is prepared by mixing graphene oxide and deionized water in a mass ratio of 1:(350-450), ultrasonically dispersing for 25-35 minutes, adding hydrobromic acid in an amount of 45-55 times the mass of the graphene oxide, stirring at 30-40° C. and 300-500 rpm for 9-11 hours, adding oxalic acid in an amount of 10-20 times the mass of the graphene oxide, heating to 60-80° C. and continuing to stir for 4-6 hours, naturally cooling to room temperature, filtering, washing with deionized water for 3-5 times, and drying at 50-60° C. for 19-21 hours.

4. The method for preparing a skin-friendly antistatic fiber fabric according to claim 2, characterized in that: The modified graphene oxide in step (2) is prepared by mixing carboxylated graphene oxide, 4-amino-1-allylpyrazole, N,N'-dicyclohexylcarbodiimide and N,N-dimethylformamide in a mass ratio of 1:(7-8):(14-15):(900-1100), ultrasonically dispersing at 20-30° C. for 15-25 min, stirring at 55-65° C. and 200-400 rpm for 23-25 ​​h, naturally cooling to room temperature and then centrifuging, washing with N,N-dimethylformamide and deionized water for 3-5 times respectively, and freeze-drying.

5. The method for preparing a skin-friendly antistatic fiber fabric according to claim 2, characterized in that: The modified polyacrylonitrile in step (3) is prepared by mixing polyacrylonitrile, sodium hydroxide and deionized water in a mass ratio of 1: (9-11): (95-105), stirring at 65-75°C and 100-300 rpm for 1-3 hours, naturally cooling to room temperature and filtering, washing with anhydrous ethanol and deionized water for 3-5 times respectively, and drying at 55-65°C for 11-13 hours to obtain pre-modified polyacrylonitrile; then, pre-modified polyacrylonitrile, (2-aminoethyl) trimethylammonium chloride hydrochloride, 5-norbornene-2-methylamine and toluene in a mass ratio of 1: (5-7): (5-6): (90-110) are mixed, refluxed at 65-75°C for 11-13 hours, naturally cooling to room temperature and filtering, washing with anhydrous ethanol and deionized water for 3-5 times respectively, and drying at 55-65°C for 11-13 hours to obtain.

6. The method for preparing a skin-friendly antistatic fiber fabric according to claim 2, characterized in that: The core-spun yarn in step (4) is prepared by mixing modified polyacrylonitrile, norbornene, modified graphene oxide, dicumyl peroxide and N,N-dimethylformamide in a mass ratio of 1: (0.02-0.04): (0.03-0.05): (0.01-0.02): (8-9) to obtain a spinning solution; the spinning solution is then electrospun, twisted with a cotton yarn core, allowed to stand at 50-60° C. for 3-5 hours, washed with deionized water for 3-5 times, and dried at 55-65° C. for 11-13 hours.

7. The method for preparing a skin-friendly antistatic fiber fabric according to claim 2, characterized in that: The process parameters of the electrospinning in step (4) are: solution flow rate 1.1~1.3ml / h, spinning voltage 9.7~9.9kv, spinning distance 15~25cm, collecting distance 10~18cm, receiving ring speed 300~600r / min, winding speed 1~3m / min, temperature 21~25℃, and humidity 55~65%.

8. The method for preparing a skin-friendly antistatic fiber fabric according to claim 2, characterized in that: The skin-friendly antistatic fiber fabric in step (5) is made by immersing the core-spun yarn in a hyaluronic acid mixture for 10 to 20 minutes, taking it out, drying it until no droplets fall within 5 to 15 seconds, standing it at 40 to 50° C. for 6 to 8 hours, washing it with deionized water for 3 to 5 times, and drying it at 55 to 65° C. for 11 to 13 hours to obtain a spun yarn; and then weaving the spun yarn with a Santoni seamless knitting underwear machine SM8-TOP2 into a warp density of 550 to 650 yarns / 10 cm, a weft density of 450 to 550 yarns / 10 cm, and a thickness of 200 to 300 g / m 2 A single-layer plain weave fabric is obtained.

9. The method for preparing a skin-friendly antistatic fiber fabric according to claim 8, characterized in that: The hyaluronic acid mixed solution is obtained by mixing hyaluronic acid, copper chloride and deionized water in a mass ratio of 1: (0.1-0.3): (8-10), and adding acetic acid solution with a mass fraction of 4%-6% to adjust the pH of the solution to 4-5.

10. Use of the skin-friendly antistatic fiber fabric according to claim 1 in seamless underwear.